Assessment of the natural history of forefoot bursae using ultrasonography in patients with rheumatoid arthritis: a twelve-month investigation. - Bowen, C; Hooper, L; Culliford, D; Dewbury, K; Sampson, M; Burridge, J; Edwards, C; Arden, N (2010)
OBJECTIVE: To determine the natural history and clinical significance of forefoot bursae over a 12-month period in patients with rheumatoid arthritis (RA). METHODS: Patients with RA (n=149) attending rheumatology outpatient clinics were assessed at baseline. A total of 120 participants, mean±SD age 60.7±12.1 years and mean±SD disease duration 12.99±10.4 years, completed the 12-month followup (98 women, 22 men, 93 rheumatoid factor positive, 24 rheumatoid factor negative, and 3 unknown). Musculoskeletal ultrasound (US) was used to identify forefoot bursae in all of the participants. Clinical markers of disease activity (well-being visual analog scale [VAS], erythrocyte sedimentation rate [ESR], C-reactive protein [CRP] level, and Disease Activity Score in 28 joints [DAS28]) and foot symptoms on the Leeds Foot Impact Scale (LFIS) Questionnaire were recorded on both occasions. RESULTS: Presence of US-detectable forefoot bursae was identified in 93.3% of returnee (n=120) participants (individual mean 3.7, range 0-11) at baseline. Significant associations were identified between bursae presence and patient-reported foot impact for impairment/footwear (LFISIF ; baseline: r=0.226, P=0.013 and 12 months: r=0.236, P=0.009) and activity limitation/participation restriction (LFISAP; baseline: r=0.254, P=0.005 and 12 months: r=0.235, P=0.010). After 12 months, 42.5% of participants had an increase in the number of US-detectable forefoot bursae and 45% of participants had a decrease. Changes in bursae number significantly correlated with changes in LFISIF (r=0.216, P=0.018) and LFISAP (r=0.193, P=0.036). No significant associations were identified between changes in bursae and changes in global well-being VAS, ESR, CRP level, or DAS28. CONCLUSION: The findings of this study suggest that forefoot bursae may regress or hypertrophy over time in patients with RA, and that these changes may be associated with self-reported foot impairment and activity restriction.